Effect of vitamin E and selenium supplementation on oxidative markers and semen quality parameters in breeding bulls - CHAND, N; TYAGI, S; SIROHI, A S; PATIL, N V; SHARMA, A; SARIKA, SARIKA (The Indian Journal of Animal Sciences, 2021)
The objective of the study was to evaluate the effect of vitamin E and Se supplementation on oxidative markers and semen quality parameters in breeding bulls. The study was conducted at ICAR-Central Institute for Research on Cattle, Meerut (subtropical climate), Uttar Pradesh during 2019. Eighteen bulls (six good bulls and twelve poor bulls) were divided into three groups consisting 6 bulls in each. Six good bulls of group 1 served as healthy control. Group 2 poor bulls were administered Vitamin E and Selenium @ 10 ml SC (Vitamin E 50 mg as DL-Î±-tocopheryl acetate and Selenium 15 mg as sodium selenite) once weekly for three weeks while group 3 poor bulls were kept as untreated control. Semen samples were collected and semen quality and biochemical parameters were done using standard procedures at fortnightly interval upto two months. Significantly low MDA and higher SOD and catalase were observed in bulls of supplemented group. Semen volume, sperm concentration, initial motility, percentage of live sperm and hypo-osmotic swelling test improved significantly in supplemented group as compared to nonsupplemented bulls. The study concludes that supplementation of vitamin E and Se causes significant improvement in oxidative stress markers and semen quality parameters in breeding bulls.